Industrial training report: Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN), Wilayah Persekutuan / Nurin Batrisya Rahmansah - Rahmansah, Nurin Batrisya (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is about the tasks and activities I completed throughout my eight weeks of industrial training at the administration department are explained in this report. In order to complete the requirements given by Universiti Teknologi Mara (UiTM), I worked under the supervision of Mr. Khayrul Nizam Bin Kamarol Zaman during my training, which took place from July 22, 2024, to September 13, 2024. I work as an intern at Lembaga Penduduk dan Pembangunan Keluarga Negara (LPPKN), Wilayah Persekutuan. Students who receive industrial training gain invaluable practical experience that helps them build skills related to their field of study. The format and guidelines established by my lecturer supervisor and Universiti Teknologi Mara (UITM) are followed in the contents of this report that I have submitted. I have highlighted my training experience and talents, as well as the difficulties I encountered and the steps I took to overcome them, in this report. I learnt more about how government agencies operate internally and developed a deeper comprehension of administrative procedures as a result of this experience, which will help me in my future profession.